Developing a partnership to improve health care delivery to children <18 years with cancer and blood disorders in the English-speaking Caribbean: lessons from the SickKids-Caribbean Initiative (SCI) - Michelle Reece-Mills; Curt Bodkyn; Jo-Anna B. Baxter; Upton Allen; Cheryl Alexis; Chantelle Browne-Farmer; Jenna Craig; Stephanie de Young; Avram Denburg; Kevon Dindial; Bonnie Fleming-Carroll; Tracey Gibson; et al. (Elsevier, 2023)
Summary: In 2013, the SickKids-Caribbean Initiative (SCI) was formalised among The Hospital for Sick Children in Toronto, Canada, the University of the West Indies, and Ministries of Health in six Caribbean countries (Barbados, The Bahamas, Jamaica, St. Lucia, St. Vincent and the Grenadines, and Trinidad and Tobago). The aim was to improve the outcomes and quality of life of children (<18 years) with cancer and blood disorders in the partner countries. Core activities included filling a human resource gap by training paediatric haematologists/oncologists and specialised registered nurses; improving capacity to diagnose and treat diverse haematology/oncology cases; developing and maintaining paediatric oncology databases; creating ongoing advocacy activities with international agencies, decision makers, and civil society; and establishing an integrated administration, management, and funding structure. We describe core program components, successes, and challenges to inform others seeking to improve health service delivery in a multidisciplinary and complex partnership.